Six-minute walking test distance predicts readmission in hospitalized heart failure patient in integrated cardiac centre, Makassar, Indonesia - Mappangara, Idar; Kabo, Peter; Amir, Muzakkir; Djafar, Zaenab; Warliani, Melda; Mustafa, Asni (International Journal of Research in Medical Sciences, 2020)
Background: Assessment of functional capacity prior to discharge can help identify patients at risk for readmissions in heart failure patients. This research aims to conduct a study in order to assess the distance traveled in the six-minute walk test (6-MWT) as a predictor of readmission rates in patients with congestive heart failure. Methods: This type of research is a quantitative correlational study with a prospective cohort study experimental design. Data were collected when the patient was treated at the Integrated Cardiac Center of Wahidin Sudirohusodo Hospital with a diagnosis of heart failure. The research was conducted from June 2019 to December 2019 after obtaining clearance from the institutional ethical committee. 6-MWT measures the distance that a patient can quickly walk on a flat, hard surface in a period of 6-MWD. To see the correlation between the components of 6-MWT the readmission using one-way anova. To determine the cut-off point, sensitivity and specificity of each component of the 6-MWT to rehospitalization using the receiver operating characteristic (ROC) curve. Statistical analysis was carried out using SPSS and SAP programs. Results: Out of the 93 samples, the 6-MWD has a significant p<0.001 for the readmission incidence≤30 days, meaning that the higher the 6-MWT value, it correlates with the decrease in the number of readmission incidents. In the ROC curve analysis for the 6-MWD parameter, it was found that the 6-MWD had a good predictability of readmission events in≤30 days (C=0.781, p<0.001). Conclusions: 6-MWD can be used to predict readmissions in≤30 days in heart failure patients. The lower the 6-MWD with a cut off of 183 meters, the higher the risk of readmission in≤30 days of heart failure patients. By knowing the cut off value, 6-MWD can be used as a reference to create a comprehensive treatment flow for heart failure patients to prevent increased readmission rates. In the end, it can reduce the burden of treatment costs on heart failure patients.